MODFLOW DAN FEFLOW UNTUK PEMODELAN HIDROGEOLOGI PADA AREA TAMBANG BATUBARA DI KALIMANTAN SELATAN - Jarwanto, Jarwanto; Arie Noor Rakhman, (Nusantara Hasana Journal, 2025)
This study aims to compare the capabilities of MODFLOW and FEFLOW software in modeling groundwater flow in open-pit mining environments with complex geometries. The method includes literature review, technical feature analysis of both software, and evaluation of simulation performance based on hydrogeological parameters and geospatial conditions. The results show that MODFLOW offers advantages in accessibility due to its open-source nature and is efficient for mining areas with relatively simple geometries. However, its limitation in grid flexibility reduces its ability to accurately represent complex morphologies and geological structures. In contrast, FEFLOW provides higher flexibility through an unstructured mesh system and integrates saturated–unsaturated flow in a single model, making it more suitable for advanced hydrogeological modeling. FEFLOW's capability to represent irregular mining geometries, simulate chemical reactions, and provide 3D visualizations is highly relevant for mining conditions in Indonesia, although it is limited by higher computational demand and licensing costs. This study offers valuable insights into selecting groundwater modeling software based on geological complexity and mining analysis objectives.